A computer system for processing data from routine pulmonary function tests. Issue 3 (June 1977) - Pack, A I; McCusker, R; Moran, F
Abstract : In larger pulmonary function laboratories there is a need for computerised techniques of data processing. A flexible computer system, which is used routinely, is described. The system processes data from a relatively large range of tests. Two types of output are produced--one for laboratory purposes, and one for return to the referring physician. The system adds an automatic interpretative report for each set of results. In developing the interpretative system it has been necessary to utilise a number of arbitrary definitions. The present terminology for reporting pulmonary function tests has limitations. The computer interpretation system affords the opportunity to take account of known interaction between measurements of function and different pathological states.